2010
DOI: 10.1063/1.3309407
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the electronic and optical properties of Na0.5Bi0.5TiO3 lead-free piezoelectric crystal

Abstract: First-principles calculation is used to study the structural, electronic, and optical properties of Na 0.5 Bi 0.5 TiO 3 ͑NBT͒ lead-free piezoelectric crystal. The band structure calculation reveals that NBT has a direct band gap of 2.1 eV. The calculated imaginary part of dielectric function indicates interband transition mainly from O 2p valence bands to Ti 3d and Bi 6p conduction bands in the low-energy region. The calculated absorption spectrum is in agreement with the available experimental data. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…It should be noted that recording well saturated loops in NBT is difficult because of the large coercive field and relatively large conducting nature of NBT. 17 The P s and P r values for NBT are 34.5 lC/cm 2 and 27 lC/cm 2 , respectively. It can also be observed from Fig.…”
mentioning
confidence: 93%
“…It should be noted that recording well saturated loops in NBT is difficult because of the large coercive field and relatively large conducting nature of NBT. 17 The P s and P r values for NBT are 34.5 lC/cm 2 and 27 lC/cm 2 , respectively. It can also be observed from Fig.…”
mentioning
confidence: 93%
“…Thus, E g can be evaluated by extrapolating the linear portion of the curve or tail from the intercept of (αhν) 1/n versus the photon energy hν. A calculation of the electronic band structure showed that Bi 0.5 Na 0.5 TiO 3 has a direct band gap of 2.1 eV, and the optical spectra of Bi 0.5 Na 0.5 TiO 3 were determined mainly by the contributions from the O 2p valence bands to the Ti 3d and Bi 6p conduction bands in the low-energy region 54 . Therefore, n = 1/2 for direct transition was used, as shown in Fig.…”
mentioning
confidence: 99%
“…Based on the fitting parameters at 300 K from Table I, the value of first CP (E cp1 ) for x=0%, 0.5%, and 0.8% is 3.56, 3.47, and 3.44 eV, respectively, mainly determined by the transitions from the O-2p VB to Ti-3d or Bi-6p lower-energy CB; the value of second one (E cp2 ) is 4.37, 4.30, and 4.26 eV, respectively, corresponding to the transition from O2p VB to Ti-3d or Bi-6p high-energy CB. 16 It indicates that the band gaps of x%-Co:NBBT6 crystals decrease with increasing Co dopants. This observation could be explained by the sp-d exchange interactions between the band electrons and localized d electrons of Co ions substituting Ti 4+ ions.…”
Section: Resultsmentioning
confidence: 97%
“…In other words, the B-site d orbitals and the O-anion 2p orbitals associated with each octahedron are the major contributors to the energy bands. 16 Other ions in the structure contribute to the higher-lying conduction states, which are of negligible importance provided the electronic polarizability, and have only a small effect on optical properties. 17 Accordingly, x%-Co:NBBT6 single crystals have similar optical absorption edges with slight differences due to different B-site (Co, Ti) cations.…”
Section: Methodsmentioning
confidence: 99%